2015
DOI: 10.1002/jso.23962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three different techniques for insertion of totally implantable venous access device: A randomized clinical trial

Abstract: The findings of our study suggest superiority of the USG approach in terms of first puncture success rate and technique failure, without increasing the procedure duration. Long-term follow-up results should help to further clarify the current debates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, there are also undoubted advantages of a percutaneous procedure, particularly since it can be performed under local anesthesia, which reduces the total procedure time (with equivalent operation times), leading to reduced costs. In addition, its safety can be significantly increased when using fluoroscopy and ultrasound, especially when the internal jugular vein is used [ 15 , 16 ]. Therefore, the percutaneous procedure (using either the internal jugular or subclavian vein) is commonly used as a reliable exit strategy in scenarios where the cutdown technique of the cephalic vein fails or as primary approach, especially by non-surgical health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also undoubted advantages of a percutaneous procedure, particularly since it can be performed under local anesthesia, which reduces the total procedure time (with equivalent operation times), leading to reduced costs. In addition, its safety can be significantly increased when using fluoroscopy and ultrasound, especially when the internal jugular vein is used [ 15 , 16 ]. Therefore, the percutaneous procedure (using either the internal jugular or subclavian vein) is commonly used as a reliable exit strategy in scenarios where the cutdown technique of the cephalic vein fails or as primary approach, especially by non-surgical health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most studied focus of port placement has been on the method of insertion, yet none have been identified as the gold standard. 8,9 We have evaluated the outcomes following 1200 port placements at a tertiary care center and have found that individual surgeons were the strongest predictors of increased operating room time, likelihood of switching to an alternative method, and procedural complications. Furthermore, for the surgeons who had consistently worse outcome measures, resident participation could not be blamed for their longer operating room times, need to switch to alternate methods or increased complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical guidelines make no specific recommendations regarding insertion method, 5,6 studies have shown conflicting results with regard to speed, success rates, and complication rates. 2,[7][8][9][10][11][12] And while the influence of method and anatomical site of insertion have been well documented, the role of provider-specific factors has been unexplored, and differences in provider skill and/or training may account for observed variability in the operative outcomes. Furthermore, how these procedural variations impact operating room time and efficiency is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An immediate complication was defined as an event occurring within 7 days after implantation. 17,18 Statistical analysis Demographic data were described by crude value and representative percentage. Categorical data were stratified by various factors and compared by chi-square test, while continuous data were compared with t-test.…”
Section: Data Collectionmentioning
confidence: 99%